The role of professionals in the field of aesthetics in health: A narrative review (Research, Society and Development, 2023)
The incessant quest for aesthetic beauty has become a significant part of contemporary life, influencing both men and women. However, it is essential to emphasize the importance of prior assessment and trust in the professional before any aesthetic procedure, whether facial or body. The main aim of this study is to highlight the importance of anamnesis and the competence required of professionals in the field when carrying out their work. This is a narrative review study that explores the impact of aesthetic professionals on the physical and mental health of clients, emphasizing the importance of continuous training. Articles published between 2019 and 2023 in Portuguese were selected from databases such as Google Scholar and Scielo. The research revealed that the search for aesthetics has been influenced by the media, and the importance of laboratory tests before procedures to assess the patient's state of health. In addition, there is a need for qualified professionals with ethics and good communication skills to ensure patient safety. Aesthetic treatments improve quality of life and require a detailed anamnesis and patient care. Qualified professionals, especially biomedical professionals, are vital in positively influencing the patient's image. Aesthetics should include physical and emotional health, not just appearance.